Variation in the distribution of the Antillean manatee (Trichechus manatus manatus) on the southern coast of Puerto Rico through helicopter aerial surveys - Mignucci-Giannoni, Antonio A.; Iglesias-Escabí, Chabeli; Rosario-Delestre, Raúl J.; Alsina-Guerrero, Mayela (Revista Ciencias Marinas y Costeras, 2018)
The Antillean manatee (Trichechus manatus manatus) is endangered due to anthropogenic activities, which affect both the manatee’s health and use of habitats required for their survival. The spatial distribution and use of the manatee habitat on the southern coast of Puerto Rico was obtained using helicopter aerial surveys and was related to zoogeographic, environmental and oceanographic factors. A total of 33 surveys were conducted along the southern coast from 2001 to 2015. There was a total of 488 sightings and 914 individuals, which represents 13 manatees per hour of effort, 12.4% being calves. No correlation was found between their presence and seasons, sea surface temperature, or currents. The use of freshwater and seagrass bed resources did not present a statistical relationship, but it is clear that they are part of their nature and necessary for their survival. However, the depth and degree of protection offered by the bays is decisive to predict the presence of manatees. A marked increase in the number of manatees per hour of effort between 2007 and 2015 represents a possible population growth. Given that the survival of manatees in Puerto Rico is threatened by different natural and anthropogenic factors, this study, together with studies on telemetry and habitat use, should help designate future protected areas critical for their survival.